eCM 2010
DOI: 10.22203/ecm.v020a32
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of odontogenic ameloblast-associated and amelotin during formation and regeneration of the junctional epithelium

Abstract: The junctional epithelium (JE) adheres to the tooth surface, and seals off periodontal tissues from the oral environment. This incompletely differentiated epithelium is formed initially by the fusion of the reduced enamel organ with the oral epithelium (OE). Two proteins, odontogenic ameloblast-associated (ODAM) and amelotin (AMTN), have been identified in the JE. The objective of this study was to evaluate their expression pattern during formation and regeneration of the JE. Cytokeratin 14 was used as a diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 44 publications
(49 reference statements)
0
78
0
Order By: Relevance
“…It is of particular interest that AMTN and ODAM were upregulated to a similar extent; a recent study (20) showed that AMTN and ODAM are re-expressed during gingival regeneration, and both proteins have been shown to interact (21). Therefore it is conceivable that the regulation of AMTN and ODAM in gingival cells is not independent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of particular interest that AMTN and ODAM were upregulated to a similar extent; a recent study (20) showed that AMTN and ODAM are re-expressed during gingival regeneration, and both proteins have been shown to interact (21). Therefore it is conceivable that the regulation of AMTN and ODAM in gingival cells is not independent.…”
Section: Discussionmentioning
confidence: 99%
“…The JE adheres to the tooth surface, and seals off periodontal tissues from the oral environment. It is formed initially by fusion of the reduced enamel epithelium with the oral epithelium (20), and is connected to the enamel via an inner basal lamina and hemidesmosomes (22). Two proteins, AMTN and ODAM/APIN, have been identified in the JE (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…During regeneration of JE after gingivectomy, ODAM appears first and localizes at the interface as well as among cells. Expression of AMTN is protracted and the protein appears restricted to the interface (Nishio et al 2010). Odam and Amtn genes are members of the SCPP gene cluster which has arisen from a common ancestor-the secreted protein acidic rich in cysteine like 1 (SPARCL1) gene (Kawasaki and Weiss 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Both are expressed mainly in the tooth where they are localized at cell-tooth interfaces (Moffatt et al 2006b(Moffatt et al , 2008Nishio et al 2010;Iwasaki et al 2005;Park et al 2007;SomogyiGanss et al 2011). ODAM was also shown to be highly expressed in some epithelial malignancies but not in corresponding healthy tissues Kestler et al 2008;Siddiqui et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the JE originates not from the oral epithelium but from the reduced enamel epithelium, which is the odontogenic epithelium that remains around the enamel surface of an erupting tooth10111213141516. Similarly, Nanci et al showed that both odontogenic ameloblast-associated and amelotin were expressed in the JE171819. Therefore, it seems acceptable that the origin of JE is the reduced enamel epithelium at the initial stage of tooth eruption.…”
mentioning
confidence: 95%